The impact of human resource management on job satisfaction - Dosenovic, Dragana; Zolak Poljašević , Branka (Anali Ekonomskog fakulteta u Subotici, 2021)
Although there are numerous and various factors that can affect job satisfaction, human resource management has been identified as one of the most important causes of job satisfaction. For this reason, this paper analyses the impact of human resource management and its activities on job satisfaction in various organizations in the Republic of Srpska, with the main goal to investigate and determine the existence and nature of the relationship between human resource management activities, as an independent variable, and job satisfaction, as a dependent variable. In order to analyse the observed relationship, an empirical research was conducted on a sample of 738 employees from 283 organizations from the Republic of Srpska. The research was conducted using a specially created survey questionnaire, and the reliability of the created instrument was calculated using the Cronbach’s alpha coefficient. Based on the results of the research, which were obtained by correlation analysis, the basic hypothesis was confirmed, which proved that human resource management activities have a statistically significant effect on job satisfaction. Also, all additional hypotheses, claiming that individual human resources management activities (recruitment and selection, training, development and rewarding) have a positive effect on job satisfaction, were confirmed.